The Bible Authorized King James Version - Carroll, Robert P.; Prickett, Stephen (Oxford ; New York : Oxford University Press, 2008)
The Bible is the most important book in the history of Western civilization, and also the most difficult to interpret. It has been the vehicle of continual conflict, with every interpretation reflecting passionately-held views that have affected not merely religion, but politics, art, and even science. This unique edition offers an exciting new approach to the most influential of all English biblical texts - the Authorized King James Version, complete with the Apocrypha. Its wide-ranging Introduction and the substantial notes to each book of the Bible guide the reader through the labyrinth of.
Cover; Copyright Page; Title Page; Contents; List of Maps; Acknowledgements; Introduction; Select Bibliography; THE BIBLE; The Translators to the Reader; The Epistle Dedicatory; List of Books of the Bible; THE OLD TESTAMENT; THE APOCRYPHA; THE NEW TESTAMENT; Explanatory Notes; Glossary to the Notes; Maps; Footnotes
Originally published: Oxford ; New York : Oxford University Press, 1997.
Includes bibliographical references.
Print version record.
Keywords: Bible; Bible -- Study and teaching; Bible; Bible; Apocrypha; Biblical teaching; General culture; Religion; BIBLES -- King James Version -- Text; Electronic books; Electronic books